Mobilizing Labour for the Global Coffee Market - Breman, Jan; Project Muse. (2015)
Coffee has been grown on Java for the commercial market since the early eighteenth century, when the Dutch East India Company began buying from peasant producers in the Priangan highlands. What began as a commercial transaction, however, soon became a system of compulsory production. This book shows how the Dutch East India Company mobilised land and labour, why they turned to force cultivation, and what effects the brutal system they installed had on the economy and society.
Machine generated contents note: I. The company as a territorial power -- Intrusion into the hinterland -- Retreat of princely authority -- Territorial demarcation and hierarchical structuring -- The Priangan highlands as a frontier -- Clearing the land for cultivation -- The composite peasant household -- Higher and lower-ranking chiefs -- Rendering servitude -- Peasants and their lords in the early-colonial era -- II. The introduction of forced cultivation -- A colonial mode of production -- From free trade to forced delivery -- The start of coffee cultivation -- Increasing the tribute -- Coercion and desertion -- Indigenous management -- Under the Company's control -- Tardy population growth -- Tackling `cultivation delinquency' -- III. From trading company to state enterprise -- Clashing interests -- Failing management -- After the fall of the VOC -- A conservative reformer -- Strengthening the government apparatus -- Social restructuring -- Stepping up corvee services.
Includes bibliographical references (pages 381-401) and index.
Description based on print version record.
Keywords: Forced labor; Coffee industry; HISTORY -- General; HISTORY -- Asia -- General; Coffee industry -- Indonesia -- Java -- History; Forced labor -- Indonesia -- Java -- History; Indonesia -- Java; History; Electronic books; Electronic books